Development of the Traditional Engklek Game Model to Improve Dental and Oral Disease Prevention Behavior in Elementary School Children - Lestari, Fuji; Djamil, Masrifan; Wiyatini, Tri (Journal of Drug Delivery and Therapeutics, 2022)
Background: Maintenance of dental and oral health as well as dental health development, especially in the group of school children, need special attention, at the age of the child is undergoing the process of growth and development and the condition of the previous teeth will affect the development of dental health in adulthood. Efforts that can be made to attract children’s attention in learning are new learning methods so that they do not cause boredom, such as the use of traditional games as learning media. The traditional game used is the traditional engklek game which has been modified and is expected to attract children’s attention and not cause boredom in learning. Research Objectives: To produce a modified game of the Fule’s version of the Fule’s Traditional Engklek Game as a learning medium to improve the behavior of preventing dental and oral diseases in elementary school children. Research Methods: The method used in this research is Research and Development (R&D). There are five stages, namely: information gathering, product/model design, expert validation and revision, product/model trial, and product/model results. The samples used were 27 children in the control group and 27 children in the intervention group. The results of the data obtained were tested using ANOVA, Shapiro Wilk, Wilcoxon test, Mann-Whitney test. Result: "Fule’s Version of the Traditional Engklek Game" is effective as a medium for behavioral change to prevent dental and oral diseases in elementary school children with a value of 0.000. Knowledge with a value of 0.000, attitudes with a value of 0.000, and actions with a value of 0.000. There is a difference in the effectiveness of the "Fule’s Traditional Engklek Game" with flipcharts on behavioral changes in preventing dental and oral diseases in elementary school children.